Effect of Website Quality and Experience on Performance Expectancy Trough E-Commerce X In Indonesia - Sondakh, Oliandes (International Journal of Scientific Research and Management (IJSRM), 2020)
In 2019, the number of internet users in Indonesia is projected to reach 175 million, or about 65.3% of the total population of Indonesia which is estimated to reach 268 million. The survey results published by the Indonesian Internet Service Providers Association (2016) show that as many as 123.5 million Indonesians use the internet to access commercial content. The high level of access to commercial content in Indonesia is a great opportunity to start e-commerce. Research conducted by Loureiro and Amorim (2017) shows that perceived website quality and experience greatly influences the judgment of a user on e-commerce performance expectancy. This research uses 130 loyal customers from well-known e-commerce in Indonesia. Non probability sampling with purposive sampling technique is used to collect data to ensure the suitability of respondents with the purpose of the study. To be a sample, respondents must have used e-commerce at least 2 times in the past 1 month. Based on the results of the study, it was concluded that website quality had a significant effect on experience, but was not significant for performance expectancy; experience has a significant effect on performance expectancy.